A Systematic Review of STEM Education Implementation in Indonesian High Schools: Opportunities, Challenges, and Policy Recommendations - Cahyanti, Necta Ayu; Suyanto, Slamet; Wantara, Ngade; Begimbetova, Guldana A.; Uanayah, Habibatul; Khilafah, M. Rasyid Nur (Jurnal Pendidikan MIPA, 2024)
The purpose of this study is to analyze the implementation of the STEM approach (Science, Technology, Engineering, and Mathematics) in Indonesia, particularly in high schools, through a systematic literature review. STEM is recognized as an innovative learning method that integrates various disciplines to enhance 21st-century skills, such as critical thinking, problem-solving, and student creativity. The analysis reveals that the implementation of STEM positively impacts student outcomes, interest, and motivation, especially in project-based and technology-driven learning. However, several challenges persist, including limited facilities, insufficient teacher training, and unequal access to technology in certain regions. To ensure the sustainability of STEM implementation, strategies should include the development of a flexible curriculum, intensive training for teachers, and collaboration with industry and private sectors. This study underscores that, with proper management, STEM-based learning holds significant potential to improve the quality of education in Indonesia, particularly at the high school level, and to prepare students for the challenges of the modern era. The findings of this study are expected to serve as a reference for designing more innovative and inclusive educational policies and practices.       Keywords: implementation, STEM, high school, indonesia, literature review.DOI: http://dx.doi.org/10.23960/jpmipa/v25i3.pp1428-1443